2018
DOI: 10.1016/j.joco.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Objective quantification of corneal haziness using anterior segment optical coherence tomography

Abstract: PurposeTo quantify normal corneal transparency by anterior segment optical coherence tomography (AS-OCT) by measuring the average pixel intensity. To analyze the variation in the average pixel intensity in mild and severe grades of corneal opacities.MethodsThis is an observational, cross-sectional study of 38 eyes from 19 patients with mild or severe grades of corneal opacities greater than 3 mm and a normal contralateral cornea. AS-OCT was performed centered on the opacity with a 3 mm cruciate protocol. A sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Of note, although SMILE reported no adverse effects on corneal endothelial cells [17] , careful evaluation by specular microscope preoperatively, or even long-term follow- AS-OCT is an effective approach to detect morphological changes such as corneal atrophy or corneal edema according to the optical density [18][19] . Corneal transparency and grades of corneal opacities can be quantified using AS-OCT [20] . In this work, AS-OCT was applied to confirm the depth, area, and density of corneal opacity to assist the surgery design.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, although SMILE reported no adverse effects on corneal endothelial cells [17] , careful evaluation by specular microscope preoperatively, or even long-term follow- AS-OCT is an effective approach to detect morphological changes such as corneal atrophy or corneal edema according to the optical density [18][19] . Corneal transparency and grades of corneal opacities can be quantified using AS-OCT [20] . In this work, AS-OCT was applied to confirm the depth, area, and density of corneal opacity to assist the surgery design.…”
Section: Discussionmentioning
confidence: 99%
“…Other modalities, such as OCT have been attempted for this purpose in the past, however, to date, there exists no standardized, validated, integrated OCT opacity analysis system with which to analyze the imaged cornea. 2 …”
Section: Discussionmentioning
confidence: 99%
“…One example of a density scale utilized in clinical care is categorizing corneal opacities into three grades: nebular, macular and leucoma. 2 , 3 This subjective qualitative system evaluates not only the density of the opacification but also the practitioner's ability to visualize iris architecture details, which may be obscured by the corneal pathology. Many clinicians instead prefer a numerical subjective system that is used to grade the corneal opacity from zero (clear cornea) to three (dense opacity), which relies on categorizing the opacity by both the density and the ability to visualize the underlying intraocular structures.…”
Section: Introductionmentioning
confidence: 99%
“…If the resolution is high enough, OCT can reveal lakes of water between the lamellas [14]. In vivo studies demonstrated that analyzing the backscattered light from OCT corneal images enables corneal transparency to be quantified [15]. When the average measured pixel intensity of a cornea which had lost transparency was compared with that of a normal cornea, average pixel intensity was shown to vary significantly with varying corneal opacification.…”
Section: Review Of Techniques For Quantifying Corneal Transparencymentioning
confidence: 99%